The Design of Rowing Ergometer Based on the Anthropometry of Acehnese Male Athletes. Issue 1 (September 2020) - Hasanuddin, I; Husaini,; Rizki, M N; Akhyar,; Nasruddin, M; Amir, N; Marlina, Y; Asmawati, L
Abstract: A rowing athlete requires effective and systematic physical training. Thus, an ergometer is very influential on the endurance of an athlete's body and becomes a vehicle of simulating groundwater rowing. However, the ergometer tool currently used has no specifications and dimensions that are in accordance with the anthropometry of male rowing athletes in Aceh. Based on these conditions, the rowing ergometer tool will be designed based on the anthropometry of rowing athletes in Aceh. Data retrieval was done by taking samples from six male rowing athletes. The data were then tested for the level of trust, accuracy, uniformity, and adequacy. From the results of data analysis, the design of the ergometer tool was in accordance with the anthropometry of male rowing athletes in Aceh. This situation can build comfort for male athletes and increase the endurance of their muscles. This includes maintaining the tempo of rowing and being able to move oars with long distances in a short time.